The impact of psychological education on the motivation for participating in physical activities among pedagogical students in Vietnam - Quoc Khanh, Mai; Kien, Phan Trung; Tinh, Tran Trung (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study investigated the impact of psychological education on enhancing the motivation of pedagogical students to participate in physical activities at three major universities in Hanoi: Hanoi National University of Education (HNUE), Hanoi Metropolitan University (HMU), and National Academy of Education Management (NAEM). The research applied Self-Determination Theory (SDT), emphasizing three fundamental psychological needs—autonomy, competence, and relatedness—to foster intrinsic motivation. Data were collected from 450 students and 30 faculty members using mixed-methods research. The findings revealed significant improvements in students’ intrinsic motivation following the intervention, particularly at HNUE (increasing from 3.9 to 5.4). Amotivation decreased substantially across all institutions, with the largest reduction observed at HNUE (from 2.4 to 1.2). Social support from peers and faculty emerged as a key factor in enhancing intrinsic motivation and reducing amotivation, particularly among female students and first- and second-year cohorts. The study highlights the critical role of psychological education in developing more effective physical education programs. It provides a practical foundation for advancing psychological education interventions to promote sustainable motivation and long-term health benefits for pedagogical students in Vietnam.